Towards Achieving Economic Freedom: Enforcing the Principle of Competition Freedom through Suppressing Anti-competitive Practices - Khedidji, Brahim; Nedjah, Issam (Journal of Legal Studies and Researches, 2024)
This study endeavors to elucidate the practices in which economic operators might engage that potentially undermine free competition, and it explores the mechanisms designed to combat and deter such practices. This investigation is driven by the question: How effective are the mechanisms that legislators have enacted to safeguard the principle of free competition in realizing economic freedom?